2007
DOI: 10.1089/ten.2006.0181
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Allogeneic Chondrocytes Cultured in Fibroin Sponge and Stirring Chamber to Promote Cartilage Regeneration

Abstract: Cartilage regeneration using a fibroin sponge and a stirring chamber was investigated to improve the potential of articular cartilage tissue engineering. Chondrocytes seeded on the fibroin-sponge scaffolds were cultured in the stirring chamber (a bioreactor facilitating mechanical stimulation) for up to 3 weeks. Changes in DNA content, glycosaminoglycan (GAG) amount, integrin subunits alpha5 and beta1 fluorescence intensity, and morphologic appearance, were studied to evaluate tissue maturity. Seeded scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…However, there is risk of infection and antigenicity. Although the risk of antigenicity seems to be absent in few studies, it needs further evaluation [23]. Osteochondral autograft transfer (OAT) also has the disadvantage of inferior mechanical properties and donor site morbidity although only a single surgical procedure is required [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is risk of infection and antigenicity. Although the risk of antigenicity seems to be absent in few studies, it needs further evaluation [23]. Osteochondral autograft transfer (OAT) also has the disadvantage of inferior mechanical properties and donor site morbidity although only a single surgical procedure is required [5].…”
Section: Discussionmentioning
confidence: 99%
“…37 The mechanical properties of fibroin sponges can be adjusted, 21,50 which can be advantageous for protecting repairing tissue from severe mechanical stress. In addition, our previous reports 3,21,36,40,44 suggested that fibroin sponge would be a functional scaffold for cartilage regeneration, in which chondrocytes tend to form aggregates and cartilage tissue with a layered structure without losing their phenotypic character or differentiation ability. 9,13 It has also been reported to be possible to modify the structure of fibroin sponge through the transgenic modification of silkworms.…”
Section: Introductionmentioning
confidence: 95%
“…50 Cell culture in fibroin sponges In vitro culturing was performed using the same types of materials as reported previously. 3,21,36,40,44 Briefly, as outlined in Figure 2, articular cartilage slices were aseptically harvested from the proximal humerus, distal femur, and proximal tibia of 4-week-old male Japanese white rabbits or from 4-week-old male CAG/EGFP transgenic Japanese white rabbits (GFP transgenic rabbits). After the removal of all FIGURE 1.…”
Section: Preparation Of Fibroin Spongesmentioning
confidence: 99%
“…The in vitro engineering of tissues, which are natively exposed to mechanical cues in vivo, has frequently been reported to be enhanced by means of bioreactors enabling mechanical conditioning, namely cyclic tension (tendons, ligaments, skeletal muscle tissue, [54][55][56] cardiac tissue [57] ), compression (cartilage [58,59] ), and bending (bone [60] ). Moreover, specific and orderly tissue structures have been induced in vitro via the dynamic conditioning of engineered constructs, [20,[61][62][63] showing once again the tight correlation existing in nature between the structure and function of biological tissues (the spatial arrangement of load-bearing structures in long bones and the presence of tightly parallel arrays of fibers in skeletal muscles being just two examples of this principle). Studies have also demonstrated intriguing findings regarding the effect of electrical stimulation on the development of excitable tissues were derived by conditioning skeletal muscle [56,64] and cardiac constructs.…”
Section: Physical Conditioning Of Developing Tissuesmentioning
confidence: 99%